Exchange rate risk, distribution asymmetry and deviations from purchasing power parity - Michael Georgiou Arghyrou; Wenna Lu; Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2020)
Firstly, we show that domestic prices of net importer countries incorporate a risk premium, driven by higher moments of future nominal exchange rate returns and secondly, using US dollar exchange rates against three currencies of major net exporting countries to the US such as Canada, Japan and the European Union, we find that the skewness of the future nominal exchange rate is the major and statistically robust moment-based factor of the deviations from purchasing power parity (PPP). Our estimates further suggest that only low and moderate exchange rate risks induce risk premia that drive deviations from PPP.
Keywords: G15; F31; F41; 330; Purchasing Power Parity; risk-aversion; exchange rate; downside risk